CALCULATION OF THE HYDRAULIC BOOM LIFTING MECHANISM WHILE LOWERING PROCESS - G. Yu. Zubrilov; V. G. Melnikov; V. A. Zeer; D. S. Golubtsov (Вестник СибАДИ, 2019)
Introduction. The paper considers the throttle regulation providing flow continuity of working fluid for the purpose of cavitations’ prevention. The throttle regulation in a hydraulic actuator of the load-lifting mechanism under the influence of static and dynamic loads taking into account elastic deformations of a hydraulic system while the boom lowering with a load is an important process. The boom lowering is carried out by the working fluid supply in a stocked cavity of a cylinder by the pump of constant productivity; draining of working fluid is made through the one-sided action throttle.Materials and methods. The consumption of working fluid from a piston cavity provided the constant movement speed of the piston without external loading change. Regulation of speed while the boom lowering was carried out by change of effective section of the throttle opening in pressure. The authors used dynamics of hydraulic actuators, mechanisms and machines, resistance of materials and differential equations.Results. The presented technique allowed determining the value of the working fluid pressure and its change in the throttle. Moreover, this technique determined the area of the throttle providing flow continuity while the boom lowering, depending on design features of the kinematic scheme of the loadlifting mechanism, on the mass of the lowered load and technology equipment, on the angular arrow acceleration and on elastic modulus of hydraulic system elements.